2012
DOI: 10.1590/s1415-65552012000400005
|View full text |Cite
|
Sign up to set email alerts
|

Políticas de gestão de pessoas, confiança e bem-estar: estudo em uma multinacional

Abstract: Os principais autores da área de Gestão de Pessoas (GP), como Legge (2006) e Wilkinson, Bacon, Redman e Snell (2010), concordam que as pessoas assumiram papel estratégico e relevante nas organizações. Considerando que as políticas de GP precisam contribuir para um maior bem-estar e fortalecer a confiança dos colaboradores nas organizações (Mariotti & Souza, 2009; Nishii, Lepak, & Schneider, 2008; Turner, Huemann, & Keegan, 2008), esta pesquisa propôs-se a avaliar a relação existente entre essas var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
34

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 39 publications
2
17
0
34
Order By: Relevance
“…This study has shown this strong association between well-being and HRM practices, confirming previous studies (Horta et al, 2012;Nishii et al, 2008). Considering that the literature on the antecedents of well-being at work has been focused mainly on studies involving the affective well-being dimension only or have tended to mix the antecedents or related variables with well-being at work (Paschoal et al, 2010), the scale proposed here offers an alternative measure to fill the gap in the literature.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study has shown this strong association between well-being and HRM practices, confirming previous studies (Horta et al, 2012;Nishii et al, 2008). Considering that the literature on the antecedents of well-being at work has been focused mainly on studies involving the affective well-being dimension only or have tended to mix the antecedents or related variables with well-being at work (Paschoal et al, 2010), the scale proposed here offers an alternative measure to fill the gap in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…The relatively high variance extracted for each factor compared to the square of the correlations between the factors indicated good discriminant validity (Table 2). the instrument developed by Siqueira and Padovam (2008), for instance, Horta, Demo, and Roure (2012) found an association between HRM policies and well-being at work. Therefore, in the current context, nomological validity would be demonstrated if the scores for the HRM policies and practices measures were positively and significantly correlated with well-being at work.…”
Section: Study 2: Confirmatory Factor Analysis and Construct Validitymentioning
confidence: 99%
“…Os resultados deste estudo possuem semelhanças com estudos já citados, que encontraram correlações signifi cativas entre Civismo e Valores, Civismo e Confi ança, Valores e Confi ança Organizacionais (Almeida & Ferreira, 2010;Chiuzi, 2006;Guardani et al, 2013;Horta, Demo, & Roure, 2012;Jardim, 2009;Ozer, 2011;Podsakoff et al, 2009;Podsakoff, et al, 2011). Ainda, este trabalho corrobora as informações contidas na literatura que apontam para o peso explicativo das variáveis Valores e Confi ança Organizacionais na predição de Civismo Organizacional.…”
Section: Resultsunclassified
“…No Estado do Rio de Janeiro, especificamente, esse segmento contribuiu com 1,2 % do volume total de vendas no mês, e com 3,2% do volume total de vendas anual. Contudo, os estudos brasileiros sobre bem-estar no trabalho têm privilegiado os grupos ocupacionais pertencentes aos setores da saúde (Gouveia, Lins, Lima, Freires, & Gomes, 2009;Ruviaro & Bardagi, 2010), da educação (Rocha Sobrinho & Porto, 2012;Traldi & Demo, 2012) e da indústria (Horta, Demo, & Roure, 2012), bem como ao setor público (Paschoal, Torres, & Porto, 2010 A satisfação no trabalho é por vezes considerada como um estado puramente afetivo e, por vezes como um fenômeno cognitivo-afetivo (Weiss, 2002). Desse modo, Locke (1976) afirma que a satisfação no trabalho consiste em um estado emocional positivo, resultante de avaliações do trabalhador sobre o próprio trabalho.…”
unclassified